Etika Dakwah Lim Production di Media Sosial Instagram: Tantangan dan Solusi - Rian Hidayatullah; Amalia Rosyadi Putri (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Social media has emerged as a pivotal medium for the dissemination of Islamic da'wah in the contemporary digital landscape. This study investigates how LIM Production, an Islamic preaching institution rooted in the pesantren tradition, implements da'wah ethics within its Instagram activities and the strategic approaches employed to navigate the challenges inherent in digital da'wah. Adopting a descriptive qualitative methodology with a case study approach, data were meticulously collected through direct content observation of the @limproduction Instagram account, in-depth interviews with the management team and selected audience members, and comprehensive documentation of their digital da'wah initiatives. The findings reveal that LIM Production consistently prioritizes the core Islamic values of sincerity (ikhlas), courtesy (kesantunan), and truthfulness (kebenaran) in its da'wah endeavors. Furthermore, the research identifies key challenges, including algorithmic pressures, negative comments, and the risk of message distortion, which are effectively mitigated through a multi-pronged strategy encompassing message consistency, rigorous source validation, promotion of digital literacy, and strategic collaborations. This study significantly contributes to the academic understanding of ethical and relevant da'wah strategies in the rapidly evolving social media era.